Crossbreeding does not lead to greater contribution of goats to household welfare, but improved management does - Ayalew, W.; King, J.M.; Bruns, E.W.; Rischkowsky, Barbara A. (Food and Agriculture Organization of the United Nations, 2001)
Based on the multiple utility of goats as well as multiple resources employed, broader productivity criteria were developed and applied to evaluate subsistence goat production. The results showed that, under the improved subsistence production, crossbred goats did not generate any more Unit Net Benefits than the indigenous goats for the resources of land, labour and biomass of goats used. Therefore, the hypothesis that under improved management crossbreds generate higher benefits than the indigenous goats was rejected. Similar comparisons showed that it was possible to significantly increase the overall contribution of goats to subsistence producers through improved management practices without the incentive of introducing crossbred goats.